Transitioning to low carbon and sustainable mobility - Caulfield, Brian (My University, 2020)
This report presents an investigation of existing evidence from academic research and international case studies to assess the suitability of available options and mechanisms to achieve a transition to low-carbon transport in Ireland. The report includes an extensive literature review examining international and national studies that examine innovative methods of reducing emissions from transport. It provides an appraisal of various academic papers, national and international policy documents and other similar projects that have investigated this issue in detail, in addition to examining a number of case studies, which focus on international examples that have successfully achieved marked reductions in carbon emissions from transport.Overall the report considers mitigation measures under the following headings: Electrification of private car stock, Active Modes, Public Transport and Travel Demand Management Strategies. Following a review of measures under these headings, 14 mitigation options are recommended for Ireland. These mitigation measures are rated in terms of their potential emission savings, the cost of their implementation and the time scale over which they might be expected to have real impacts on decarbonising transport.
Keywords: Environmental impacts; Transport; Sustainability; Environment; Smart planet; Smart & Sustainable Planet; Environmental Impacts of Transport; Transport